Water Quality Profiles of Fish Farms from the District Attock, Pakistan - Hadyait, Muhammad Arfan; Ali, Asif; Bhatti, Ehsan Mahmood (PSM Biological Research, 2020)
The survival and optimum growth of cultured fish largely depend upon the good water quality. The study aimed to provide an overview of fish farms in the Attock District for suitability and development of fish farming. Water samples from five sites (Garyala, Fatehjang, Hattian, Hazro, and Hassan Abdal) in triplicates were collected randomly in July 2017. The mean value and standard deviation of all the selected water quality parameters were as turbidity (96.12 ± 24.57 NTU), cadmium (0.001 ± 0.001 mg/L), chromium (0.003 ± 0.002 mg/L), lead (0.060 ± 0.012 mg/L), pH (7.78 ± 0.21), conductivity (366.66 ± 66.41 µS/cm), salinity (210.60 ± 66.86 mg/L), TDS (259.60 ± 87.33 mg/L), total alkalinity (82.16 ± 26.36 mg/L), total hardness (66.32 ± 29.16 mg/L), chloride (31.72 ± 4.28 mg/L), sulfite (19.60 ± 4.78 mg/L) and carbon dioxide (8.44 ± 2.42 mg/L)) were found to be almost within the suitable range for fish culture. Hence, this study revealed that the water quality of the Attock District can profitably be used for fish culture.